2013
DOI: 10.2174/1871527311312040005
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein Signaling, Lipid Rafts and the Possible Sites of Action for the Antidepressant Effects of n-3 Polyunsaturated Fatty Acids

Abstract: Dietary fish oil, a source of polyunsaturated fatty acids (n-3 PUFA), has become increasingly popular for antidepressant therapy, in part because about half of patients treated with conventional antidepressants either fail to remit or discontinue therapy due to side effects. The inception of n-3 PUFA as a putative depression therapeutic may have stemmed from reports suggesting that dietary n-3 PUFA deficiency is linked to both altered membrane PUFA content as well as clinical depression. Several studies have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…Since escitalopram and R-citalopram have equal lipophilicity, there is likely a lipid raft protein that acts as a binding site for antidepressants. This study also revealed that antidepressant accumulation in rafts is a slow process mirroring the time course for the invitro effects of these drugs [9,16,69]. Similarly, published findings analyzing the components of raft and non-raft membrane samples show that DHA is present in both [54].…”
Section: Mechanism Of Actionsupporting
confidence: 63%
See 1 more Smart Citation
“…Since escitalopram and R-citalopram have equal lipophilicity, there is likely a lipid raft protein that acts as a binding site for antidepressants. This study also revealed that antidepressant accumulation in rafts is a slow process mirroring the time course for the invitro effects of these drugs [9,16,69]. Similarly, published findings analyzing the components of raft and non-raft membrane samples show that DHA is present in both [54].…”
Section: Mechanism Of Actionsupporting
confidence: 63%
“…While this study did not examine heterotrimeric G proteins, a similar effect of PUFA is certainly possible. Furthermore, PUFAs are able to affect fatty acylation of several signaling proteins [8,9,17,20,49]. …”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…studies, however, suggest that PR3 has a greater role than NE in IL-1β processing and secretion. (3) PR3 is localized in the same lipid raft domains (75,76) as A1AT (5,20) and LA (77). Bilayer-bound PR3 has a reduced catalytic efficiency, whereas its inhibition by A1AT is more important than that observed for the soluble form of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several reports indicate that lower ω3-fatty-acid levels, including lower plasma EPA, and DHA, or EPA in red blood cells, predicted greater risk of suicide attempt (Hibbeln and Salem, 1995, Huan et al , 2004, Sublette et al , 2006). Because both cholesterol and DHA are major components of the lipid raft, it is possible that reduced cholesterol and ω3-fatty-acid levels may affect the formation of lipid rafts in the CNS, and subsequently reduce neurotransmitter signaling (Czysz and Rasenick, 2013). Notably, increased formation of lipid rafts in the membrane would facilitate serotonergic (Donati et al , 2008, Renner et al , 2007), dopaminergic (Villar et al ., 2009), and glutamatergic (Francesconi et al , 2009, Ponce et al , 2008) neurotransmitter signaling; all of these play important roles in the pathophysiology and treatment of psychiatric disorders.…”
Section: Oxidative Stress Cholesterol and ω3 Fatty Acids In The Patmentioning
confidence: 99%